Proposta para avaliação e modelagem de métodos de cocriação em design - Pinheiro, Luciano Tardin (2019)
The emergence of the design thinking theme in the last two decades, leveraged by the speed of digital media, has been arousing curiosity in the productive field. Today, the discussion of this approach advances as a means of systematically introducing creativity into productive environments in pursuit of innovation. It represents a practical proposal to adopt human-centered design in solving complex problems. The speed of dissemination of this theme generated familiarity with the term, but also allowed for distortions of its understanding and partial implementations, which tend to test the perception of its effectiveness. From the participative observation of these dynamics in the local context, this study proposes the construction of a conceptual infrastructure for the adoption and dissemination of design thinking which effectively conducts the local practice of human-centered design. Accordingly, four investigation processes were adopted: a theoretical research, a survey conducted in digital professional relationship groups, in-depth interviews with experts and content analysis of design toolkits, publications that disseminate methods, tools and design concepts, that are focal signs of the emerging approach to design thinking. The research results point to the need for practical infrastructure of the design thinking process, particularly in the aspect of participation and co-creation. This study brings the academic contribution of empirically assessing the spread of design thinking in the professional field, especially with regard to collaborative practices, enabling the understanding of the difficulties and potentials of their adoption in the local context. It also contributes by casting a critical eye on the publication of design toolkits and their disruptive character in the spread of design thinking.